Characterization of Pigmented Bacillus Species Isolated from Aquatic Environment - Saad Sabah Fakhry; Ahmed Ibrahim Jessim; Manal Abdulateef Hasan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2021)
The genus of Bacillus includes several group of genetically and phenotypically different. Some species of spore-forming bacteria are pigmented, although the role of these pigments has not been fully elucidated. This study aimed to isolate a new species of Bacillus species and characterize both pigmented and pigment-producing bacteria product. For this purpose, samples were used water to isolate spore-forming bacteria and verify the presence of pigmentation. All bacteria found pegmatite were characterized at the species level and one of those selected for further studies. The physiological and biochemical analysis carried out revealed that: I) the product is carotenoid pigment, II) its synthesis takes place in stationary phase of growth. These features have allowed for us to assume that the carotenoid is produced under conditions of cellular stress and probably involved in cellular adaptation to some environmental conditions are not optimal for the cell.